ASSESSMENT OF PUBLIC AWARENESS AND KNOWLEDGE OF MEDIA CAMPAIGNS ON ENVIRONMENTAL ISSUES IN SOUTH-SOUTH ZONE - Enobakhare, Josephine Osatohanmwen; Orem, Albert Echua; Ogar, Gabriel Onah (European Scientific Journal, ESJ, 2013)
This article examines public awareness and knowledge of media campaigns on environmental issues in south-south states Nigeria. It argues that media campaigns are strong instrument in public awareness on environmental issues. However the remarkable progress made by media in providing environmental information in Nigeria, there are still substantial constraints to the effective management and development of the environment. The mismanagement of environment in South-South geo-political zones has literally contributed to the problem of erosion and deforestation which has lead to deterioration of the environs. The study was anchored on two media theories- attitude change theory and social responsibility theory. Data were carefully collected through the instrumentality of questionnaire and were analyzed using tables, bar and pie charts. Findings revealed that South-south populaces were aware of sensitization campaigns about environmental management issues. It also revealed that they have a good knowledge and that their attitude in regards to environmental management has changed positively as a result of the media campaigns. Based on the findings, useful recommendations were made such as the media should not down play the issue of environmental hazards. They should play the agenda function by emphasizing on the effects of environmental degradation.